Síndrome oral-facial-digital: relato de um caso com anomalias do sistema nervoso central Oral-facial-digital syndrome: report of a case with abnormalities of the central nervous system - Gerson Carakushansky; Aluizio H. de Andrade Machado (Arquivos de Neuro-Psiquiatria)
É relatado um caso de síndrome oral-facial-digital em paciente com anomalias do sistema nervoso central. Os autores fazem um revisão da literatura a procura de outros casos em que tais anomalias também estivessem presentes. A cariotipagem foi normal. The case of a 3-month-old-female infant with oral-facial-digital malformations is reported. Ventriculogram disclosed widened lateral ventricles with lack of communication with the cisterna magna probably because of congenital defect in the formation of the aqueduct of Sylvius. There was communication with a porencephalic cyst present in the anterior fossa. A review of the literature indicates that porencephalies and hydrocephalus appear to be fairly common malformations associated with the OFD syndrome. Dermatoglyphic studies have shown an excess of whorl patterns on the digits. The karyotype was 46,XX.